Transition metal sulfide vertical structure diode and method of making same

CN116825827BActive Publication Date: 2026-10-16NANJING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310797064.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2026-10-16
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

但是垂直二极管的整流比较低或者正向导通电流较低,并没有达到垂直二极管性能预测值,二极管性能并不显著

Benefits of technology

[0022] Mechanism of Invention: The transition metal sulfide vertical structure diode of this invention forms a Schottky contact between the bottom electrode metal prepared by Grids copper mesh and the mechanically peeled molybdenum disulfide, and an ohmic contact between the top electrode metal, antimony, and molybdenum disulfide, thus forming a Schottky diode. Compared to the common electron beam lithography and ultraviolet lithography methods, which require further processing to obtain a clean surface, using Grids copper mesh can directly achieve instrument-precision-level surface cleanliness without the introduction of other impurities. This advantage greatly enhances the contact between the metal and the semiconductor, thereby further reducing the off-state current and significantly improving the rectification ratio of the vertical structure diode. Furthermore, the molybdenum disulfide thin film transferred by van der Waals transfer has many advantages, including fewer defects, a smooth surface, and high mobility. Regarding the final ohmic contact between the top electrode metal, antimony, and molybdenum disulfide, antimony has a very low work function, matching the conduction band bottom of the two-dimensional semiconductor and forming a Schottky barrier less than or equal to zero. This significantly improves the forward current and series resistance of the transition metal sulfide vertical structure diode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116825827B_ABST
    Figure CN116825827B_ABST
Patent Text Reader

Abstract

The application discloses a transition metal sulfide vertical structure diode and a preparation method thereof. The diode comprises a substrate, a bottom electrode, a transition metal sulfide film and a top electrode. The top electrode contact layer is metal antimony. The bottom electrode is fixed on the surface of the substrate by using a Grids copper net, and then metal evaporation is performed to obtain the bottom electrode. The transition metal sulfide vertical structure diode can directly obtain the surface cleanliness of the instrument precision level by using the Grids copper net, without the introduction of other impurities, and the surface is smooth. The advantage can greatly strengthen the contact between the metal and the semiconductor, and further reduce the off-state current, thereby obviously improving the rectification ratio of the vertical structure diode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a diode and its fabrication method, and more particularly to a transition metal sulfide vertical structure diode and its fabrication method. Background Technology

[0002] Layered semiconductor crystals have been extensively studied in terms of material properties and device applications. Representative transition metal chalcogenide (TMD) materials have been used in device applications such as field-effect transistors (FETs), PN diodes, Schottky diodes, photovoltaic diode circuits, FET circuits for light-emitting diodes, and ring oscillators. Most previous devices utilized the lateral electron transport properties and the ultrathin characteristics of two-dimensional semiconductor crystals. However, the ultrathin nature of two-dimensional crystals inevitably leads to high contact resistance due to their limited channel / contact volume. Furthermore, when using even thinner 2D crystals, surface adsorption and defect problems introduced during device fabrication become more pronounced.

[0003] To overcome these problems, vertical transistors and diodes have been proposed as alternative device designs for two-dimensional electronic applications. Vertically stacked layered transistors have been used in various device designs and have shown significant advantages compared to lateral devices. However, vertical diodes have relatively low rectification ratios or low forward conduction currents, failing to meet the predicted performance values, and their performance is not significant. Clearly, better interface contact results in lower contact resistance; therefore, we hypothesize that surface adsorption and defects introduced during device fabrication lead to the performance degradation. Thus, we propose improving electrode fabrication methods to reduce surface impurity adsorption and defects, which can further improve device performance. Summary of the Invention

[0004] Objectives of the invention: The first objective of this invention is to provide a transition metal sulfide vertical structure diode with optimized diode rectification ratio; the second objective of this invention is to provide a method for preparing the aforementioned transition metal sulfide vertical structure diode.

[0005] Technical solution: The transition metal sulfide vertical structure diode of the present invention includes a substrate, a bottom electrode, a transition metal sulfide thin film and a top electrode; the top electrode contact layer is made of antimony metal; the bottom electrode is fixed on the substrate surface using a copper grid and then metal is deposited by vapor deposition.

[0006] Preferably, the transition metal sulfide film is molybdenum disulfide.

[0007] Preferably, the bottom electrode contact layer is one of platinum, gold, or palladium.

[0008] Preferably, the substrate is a silicon dioxide substrate, a sapphire substrate, or a polyimide substrate with high resistance. A high-resistivity substrate allows for very low parasitic effects in the device.

[0009] The method for fabricating a transition metal sulfide vertical structure diode according to the present invention includes the following steps:

[0010] (1) Fix the Grids copper mesh on the substrate surface, then vapor deposit metal, and remove the Grids copper mesh after vapor deposition to obtain the bottom electrode;

[0011] (2) A molybdenum disulfide thin film material was obtained on a silicon dioxide wafer by mechanical peeling and covered with a polymer encapsulation layer;

[0012] (3) Remove the polymer encapsulation layer and molybdenum disulfide film from the silicon dioxide wafer and transfer them to the prepared bottom electrode. The molybdenum disulfide film is in contact with the bottom electrode and heated to make the molybdenum disulfide film tightly bonded to the bottom electrode.

[0013] (4) Using an electron beam to pattern a vertical structure diode, a top electrode metal antimony is prepared at the patterned location so that it can work independently; thus obtaining the transition metal sulfide vertical structure diode.

[0014] Preferably, in step (1), polyvinyl alcohol adhesive is used to fix the edges of the Grids copper mesh onto the substrate.

[0015] Preferably, in step (1), the evaporation conditions are: evacuation to a vacuum level higher than 10. -6 Torr, evaporation rate 0.1–0.2 angstroms per second.

[0016] Preferably, in step (2), the mechanical exfoliation method involves placing a block of molybdenum disulfide between two low-viscosity polydimethylsiloxane (PDMS) films, pressing them together, and repeating the process to transform them into thinner layered sheets. The two-dimensional materials prepared by the mechanical exfoliation method have many advantages, including fewer defects, a smooth surface, and high mobility.

[0017] Preferably, the polymer encapsulation layer is polymethyl methacrylate (PMMA) or polyvinyl alcohol.

[0018] Preferably, in step (3), the heating temperature is 100-120°C.

[0019] In step (3), a low-viscosity PDMS film is used to peel the polymer encapsulation layer and the molybdenum disulfide film from the silicon dioxide wafer and stack them onto the prepared bottom electrode. After successful stacking, the temperature is raised to make the low-viscosity PDMS film lose its adhesiveness, thereby releasing the polymer encapsulation layer and the molybdenum disulfide film.

[0020] Preferably, in step (4), the conditions for preparing the top electrode antimony metal are: evacuating to a vacuum level higher than 10. - 6 Torr, evaporation rate 0.1–0.4 angstroms per second.

[0021] The high-frequency, high-rectification-ratio transition metal sulfide vertical structure diode of this invention can be used for rectifying various high-frequency AC signals, such as sinusoidal signals and square wave signals. Specifically, after fabricating the high-frequency, high-rectification-ratio transition metal sulfide vertical structure diode, an AC signal of a specified voltage is input to the input terminal of a rectifier circuit containing the rectifier diode using a function generator, and the rectified DC signal is acquired at the output terminal using an oscilloscope.

[0022] Mechanism of Invention: The transition metal sulfide vertical structure diode of this invention forms a Schottky contact between the bottom electrode metal prepared by Grids copper mesh and the mechanically peeled molybdenum disulfide, and an ohmic contact between the top electrode metal, antimony, and molybdenum disulfide, thus forming a Schottky diode. Compared to the common electron beam lithography and ultraviolet lithography methods, which require further processing to obtain a clean surface, using Grids copper mesh can directly achieve instrument-precision-level surface cleanliness without the introduction of other impurities. This advantage greatly enhances the contact between the metal and the semiconductor, thereby further reducing the off-state current and significantly improving the rectification ratio of the vertical structure diode. Furthermore, the molybdenum disulfide thin film transferred by van der Waals transfer has many advantages, including fewer defects, a smooth surface, and high mobility. Regarding the final ohmic contact between the top electrode metal, antimony, and molybdenum disulfide, antimony has a very low work function, matching the conduction band bottom of the two-dimensional semiconductor and forming a Schottky barrier less than or equal to zero. This significantly improves the forward current and series resistance of the transition metal sulfide vertical structure diode.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The transition metal sulfide vertical structure diode can directly obtain the surface cleanliness of instrument precision by using Grids copper mesh, without the introduction of other impurities, and the surface is smooth. This advantage can greatly enhance the contact between the metal and the semiconductor, thereby further reducing the off-state current and significantly improving the rectification ratio of the vertical structure diode; (2) The diode achieves a rectification ratio of up to 10 6 The rectification ratio exceeds 1.4 × 10⁻⁶. 5 A / cm 2 (3) The unit current density is high; (4) The preparation method is simple. Attached Figure Description

[0024] Figure 1 This is a schematic diagram of the transition metal sulfide vertical structure diode prepared in Example 1;

[0025] Figure 2 This is a flowchart illustrating the fabrication process of the transition metal sulfide vertical structure diode prepared in Example 1.

[0026] Figure 3 Transmission electron microscope image of the transition metal sulfide vertical structure diode prepared in Example 1;

[0027] Figure 4 An optical microscope image of the transition metal sulfide vertical structure diode prepared in Example 1;

[0028] Figure 5 The current-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 1;

[0029] Figure 6 The rectification ratio-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 1;

[0030] Figure 7 An optical microscope image of the transition metal sulfide vertical structure diode prepared in Example 2;

[0031] Figure 8 The current-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 2;

[0032] Figure 9 The rectification ratio-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 2;

[0033] Figure 10 An optical microscope image of the transition metal sulfide vertical structure diode prepared for Comparative Example 1;

[0034] Figure 11 Current-voltage curves of the transition metal sulfide vertical structure diode prepared for Comparative Example 1;

[0035] Figure 12 The rectification ratio-voltage curve of the transition metal sulfide vertical structure diode prepared for Comparative Example 1. Detailed Implementation

[0036] The technical solution of the present invention will be further described below with reference to the embodiments.

[0037] Example 1

[0038] The transition metal sulfide vertical structure diode of the present invention has a substrate of high-resistivity silicon oxide, a bottom electrode of platinum (Pt), a transition metal sulfide thin film of molybdenum disulfide thin film, and a top electrode of antimony (Sb). The preparation method includes the following steps:

[0039] (1) A copper grid is attached to the surface of a high-resistivity silicon oxide substrate, and the edges of the copper grid are fixed with polyvinyl alcohol (PVA) adhesive. Then, a vacuum is drawn to a vacuum level higher than 10. -6 Torr, with a deposition rate of 0.1 to 0.2 Å per second, deposits 3 / 9 nm of titanium / platinum. After removing the Grids copper mesh and PVA adhesive with a tungsten needle, a smooth bottom electrode can be obtained.

[0040] (2) Molybdenum disulfide thin film material was obtained on a 275nm silicon dioxide wafer by mechanical peeling. Low-viscosity polydimethylsiloxane (PDMS) film was used. A small piece of molybdenum disulfide was placed on the PDMS film with tweezers. Then, the PDMS film was adhered to another new PDMS film. The PDMS film was pressed gently by hand and then separated. This adhesion operation was repeated 4 to 5 times to make it into a thinner layered sheet. Then, the PDMS containing the thinner layered sheet was adhered to the 275nm silicon dioxide wafer. The PDMS film was pressed gently by hand and then separated from the silicon dioxide wafer, leaving a molybdenum disulfide film on the surface of the silicon dioxide wafer. The thickness of the film was measured to be between 52 and 58 nm. Finally, a polymethyl methacrylate polymer encapsulation layer was covered on the surface.

[0041] (3) The polymer encapsulation layer and the molybdenum disulfide film were peeled off from the 275nm silicon dioxide wafer using a polydimethylsiloxane (PDMS) film with a release temperature of 100-120℃, and then aligned and stacked onto the prepared bottom electrode, with the stacking area controlled at 4µm. 2 The stacking speed is slow (Z-axis speed <1um / s); after successful stacking, the temperature is increased to release the encapsulation layer and molybdenum disulfide film from the PDMS. The heating rate is slow (<0.5℃ / min). After reaching the release temperature, the molybdenum disulfide film comes into close contact with the bottom electrode metal platinum, lifting the PDMS. The entire transfer process is carried out using a high-precision micro-transfer platform.

[0042] (4) Use 700C cm 2 A 30 keV electron beam was used to pattern a vertical structure diode, and antimony metal was fabricated as the top electrode at the patterned area. The vacuum level was then evacuated to a value higher than 10 keV. -6 Torr, evaporation rate 0.1-0.4 angstroms per second, evaporation of 20 / 25 nm antimony / gold, after removing the resist, a diode device is obtained, which can work independently;

[0043] Figure 1 This is a schematic diagram of the transition metal sulfide vertical structure diode prepared in Example 1;

[0044] Figure 2 This is a flowchart illustrating the fabrication process of the transition metal sulfide vertical structure diode prepared in Example 1.

[0045] Figure 3 The image shown is a transmission electron microscope image of the transition metal sulfide vertical structure diode prepared in Example 1. It shows that the side structure of the vertical structure diode is a platinum bottom electrode / layered molybdenum disulfide film / antimony top electrode. The contact interface between the molybdenum disulfide film and the platinum bottom electrode is clean and smooth, which provides a good foundation for realizing a pinless metal-semiconductor intrinsic contact interface.

[0046] Figure 4 This is an optical microscope image of the transition metal sulfide vertical structure diode prepared in Example 1. The overlapping area of ​​the bottom and top electrodes is only 3 μm. 2 .

[0047] Figure 5 The current-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 1 shows that the current exceeds 2.5mA at 2V, indicating that it is a high-performance molybdenum disulfide vertical structure diode.

[0048] Figure 6 The rectification ratio-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 1 shows that the maximum rectification ratio exceeds 2 × 10⁻⁶ in the 0–2V range. 6 It is a high-performance molybdenum disulfide vertical structure diode.

[0049] Example 2

[0050] The transition metal sulfide vertical structure diode of the present invention has a substrate of high-resistivity silicon oxide, a bottom electrode of palladium (Pd), a transition metal sulfide thin film of molybdenum disulfide thin film, and a top electrode of antimony (Sb). The fabrication method includes the following steps:

[0051] (1) A copper grid is attached to the surface of a high-resistivity silicon oxide substrate, and the edges of the copper grid are fixed with polyvinyl alcohol (PVA) adhesive. Then, a vacuum is drawn to a vacuum level higher than 10. -6 Torr, with a deposition rate of 0.1 to 0.2 Å per second, deposits 3 / 9 nm of titanium / palladium. After removing the Grids copper mesh and PVA adhesive with a tungsten needle, a smooth bottom electrode can be obtained.

[0052] (2) Molybdenum disulfide thin film material was obtained on a 275nm silicon dioxide wafer by mechanical peeling. Low-viscosity polydimethylsiloxane (PDMS) film was used. A small piece of molybdenum disulfide was placed on the PDMS film with tweezers. Then, the PDMS film was adhered to another new PDMS film. The PDMS film was gently pressed by hand and then separated. This adhesion operation was repeated 4-5 times to make it into a thinner layered sheet. Then, the PDMS containing the thinner layered sheet was adhered to the 275nm silicon dioxide wafer. The PDMS film was gently pressed by hand and then separated from the silicon dioxide wafer, leaving a molybdenum disulfide film on the surface of the silicon dioxide wafer. The film thickness was measured to be between 20 and 22nm. Finally, a polymethyl methacrylate polymer encapsulation layer was covered on the surface.

[0053] (3) The polymer encapsulation layer and the molybdenum disulfide film were peeled off from the 275nm silicon dioxide wafer using a polydimethylsiloxane (PDMS) film with a release temperature of 100-120℃, and then aligned and stacked onto the prepared bottom electrode, with the stacking area controlled at 4µm. 2 The stacking speed is slow (Z-axis speed <1um / s); after successful stacking, the temperature is increased to release the encapsulation layer and molybdenum disulfide film from the PDMS. The heating rate is slow (<0.5℃ / min). After reaching the release temperature, the molybdenum disulfide film comes into close contact with the bottom electrode metal palladium, lifting the PDMS. The entire transfer process is carried out using a high-precision micro-transfer platform.

[0054] (4) Use 700C cm 2 A 30 keV electron beam was used to pattern a vertical structure diode, and antimony metal was fabricated as the top electrode at the patterned area. The vacuum level was then evacuated to a value higher than 10 keV. -6 Torr, with a deposition rate of 0.1–0.4 angstroms per second, deposits 20 / 25 nm of antimony / gold. After removing the resist, a diode device is obtained, which can operate independently.

[0055] Figure 7 An optical microscope image of the transition metal sulfide vertical structure diode prepared in Example 2.

[0056] Figure 8 The current-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 2 shows that the current exceeds 2.3mA at 2V.

[0057] Figure 9 The rectification ratio-voltage curve of the transition metal sulfide vertical structure diode prepared in Example 2 shows that the maximum rectification ratio exceeds 1×10⁻⁶ in the 0–2V range. 4 .

[0058] Comparative Example 1

[0059] Based on Example 1, step (1) is changed to writing the pattern of the bottom electrode of the vertical structure diode on a high-resistivity silicon oxide substrate using electron beam lithography (EBL), with a width of 100 μm. Then, a vacuum is drawn to a vacuum level higher than 10. -6 Torr, evaporation rate 0.1-0.2 Å / s, evaporation of 3 / 9 nm titanium / platinum, after removing the resist, a patterned bottom electrode is obtained; other steps are the same as in Example 1.

[0060] Figure 10 An optical microscope image of the transition metal sulfide vertical structure diode prepared for Comparative Example 1;

[0061] Figure 11 The current-voltage curve of the transition metal sulfide vertical structure diode prepared for Comparative Example 1 shows a current of 1.3 mA at 2V, which is much lower than the current in Example 1. This indicates that the diode prepared in Comparative Example 1 has a greater resistance than the diode prepared in Example 1. This further illustrates that the preparation of the bottom electrode affects the diode performance; the larger the clean current at the bottom electrode, the better.

[0062] Figure 12 The rectification ratio-voltage curve of the transition metal sulfide vertical structure diode prepared for Comparative Example 1 shows a maximum rectification ratio of 230 in the 0–2V range, which is much lower than the rectification ratio of 2 × 10 in Example 1. 6 This further illustrates that using copper grids to fabricate metal bottom electrodes results in a cleaner, smoother surface, better contact capability, and therefore a higher rectification ratio.

Claims

1. A method for fabricating a transition metal sulfide vertical structure diode, characterized in that, Includes the following steps: (1) Fix the Grids copper mesh on the substrate surface, then vapor deposit metal, and remove the Grids copper mesh after vapor deposition to obtain the bottom electrode; (2) A molybdenum disulfide thin film material is obtained on a silicon dioxide wafer by mechanical peeling and covered with a polymer encapsulation layer; (3) Remove the polymer encapsulation layer and molybdenum disulfide film from the silicon dioxide wafer and transfer them to the prepared bottom electrode. The molybdenum disulfide film is in contact with the bottom electrode, and heating is used to make the molybdenum disulfide film tightly bonded to the bottom electrode. (4) Using an electron beam to pattern a vertical structure diode, a top electrode metal antimony is prepared at the patterned area so that it can work independently; thus obtaining the transition metal sulfide vertical structure diode. In step (1), polyvinyl alcohol adhesive is used to fix the edges of the Grids copper mesh to the substrate; In step (3), the heating temperature is 100~120℃; In step (1), the conditions for vapor deposition are: evacuation to a vacuum level higher than 10. -6 Torr, evaporation rate 0.1–0.2 angstroms per second; In step (4), the conditions for preparing the top electrode antimony metal are: evacuating to a vacuum level higher than 10. -6 Torr, evaporation rate 0.1–0.4 angstroms per second; The mechanical peeling method described in step (2) is as follows: place the block of molybdenum disulfide between two low-viscosity polydimethylsiloxane films, press them apart, and repeat the operation to make it into a thinner layered sheet.

2. A transition metal sulfide vertical structure diode, characterized in that, The diode is prepared by the method described in claim 1, comprising a substrate, a bottom electrode, a transition metal sulfide thin film, and a top electrode; the top electrode contact layer is made of antimony metal; the bottom electrode is obtained by fixing a copper grid to the substrate surface and then depositing metal thereon. The transition metal sulfide film is molybdenum disulfide; The bottom electrode contact layer is one of the following metals: platinum, gold, and palladium. The substrate is a silicon dioxide substrate, a sapphire substrate, or a polyimide substrate with high resistance.

Citation Information

Patent Citations

  • Single-layer transition metal disulfide flexible photodetector preparation method

    CN110611012A

  • Two-dimensional semiconductor-metal ohmic contact structure, preparation method and application

    CN115064588A

  • Vertical schottky barrier diodes using two-dimensional layered semiconductors and fabrication methods thereof

    US20210066511A1